1998
DOI: 10.3354/meps164237
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous imposex and organotin bioaccumulation in gastropods Nucella lapillus from Galicia (NW Spain):a possible effect of nearshore shipping

Abstract: A survey was conducted during the summer of 1996 to assess the expression, extent and impact of hnposex (a set of sexual anomalies) in 37 populations of Nucella lapillusspread over the Galician coastline (NW Spain); the bioaccumulation of several organotin (OT) species (monobutyltin. MBT; dibutyltin, DBT; tributyltin, TBT; and triphenyltin, TPhT) was also determined in 20 of those samples. While imposex, TBT (from 36 to 974 ng Sn g-' dry weight, ppb) and DBT (from 169 to 909 ppb) were detected in every sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…In South America, imposex occurrence is reported in Chile (Chorus giganteus, Xanthochorus cassidiformis, Nucella crassilabrum - Gooding et al, 1999) and Brazil (Castro et al, 2000;Fernandez et al, 1998;Magalhães et al, 1997). Information on concentration in waters (Hashimoto et al, 1998; Malaca straits), sediments (Kan-Atireklap et al, 1997a -Thailand;Ko et al, 1995 -Hong Kong;Stewart & de Mora, 1992 -Fiji Island;King et al, 1989 -New Zealand) and organisms (bivalves, Perna viridis -Kan-Atireklap et al, 1997b; Mytidus edulis and Aequipecten irradians - Guolan & Yong, 1995;gastropods, T. clavigera, Thais tuberosa and Morula granulataLiu et al, 1997) are scarce, although reported levels specially in areas including intensive navigation and harbor installations have been high (over 1,000ng.g -1 ) and of the same order as those available for temperate climate areas (Morgan et al, 1998;Ruiz et al, 1998;Swennen et al, 1997;ten Hallers-Tjabbes et al, 1994). As for the effect on humans, although organotin compounds are considered extremely toxic, environmental routes of exposure are usually not considered very critical (Schweinfurth & Günzel, 1987;Tsuda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In South America, imposex occurrence is reported in Chile (Chorus giganteus, Xanthochorus cassidiformis, Nucella crassilabrum - Gooding et al, 1999) and Brazil (Castro et al, 2000;Fernandez et al, 1998;Magalhães et al, 1997). Information on concentration in waters (Hashimoto et al, 1998; Malaca straits), sediments (Kan-Atireklap et al, 1997a -Thailand;Ko et al, 1995 -Hong Kong;Stewart & de Mora, 1992 -Fiji Island;King et al, 1989 -New Zealand) and organisms (bivalves, Perna viridis -Kan-Atireklap et al, 1997b; Mytidus edulis and Aequipecten irradians - Guolan & Yong, 1995;gastropods, T. clavigera, Thais tuberosa and Morula granulataLiu et al, 1997) are scarce, although reported levels specially in areas including intensive navigation and harbor installations have been high (over 1,000ng.g -1 ) and of the same order as those available for temperate climate areas (Morgan et al, 1998;Ruiz et al, 1998;Swennen et al, 1997;ten Hallers-Tjabbes et al, 1994). As for the effect on humans, although organotin compounds are considered extremely toxic, environmental routes of exposure are usually not considered very critical (Schweinfurth & Günzel, 1987;Tsuda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Similar improvements of imposex condition have been reported in other areas where legislative bans of TBT were effective, such as in the North Sea (Evans et al 1991, 1996, Harding et al 1997, Birchenough et al 2002a), SW England (Bryan et al 1993), Ireland (Minchin et al 1995), Australia (Rees et al 2001) and Canada (Reitsema et al 2002). Despite the same legislative ban of TBT, a reverse trend has been observed in Spain (Ruiz et al 1998, Ramon & Amor 2001 and in Portugal (Barroso & Moreira 2002, Santos et al 2002. In Thailand, where no restriction of TBT use has been introduced, imposex has increased (Bech 2002).…”
Section: Temporal Evolutionmentioning
confidence: 53%
“…Those females that were still fertile had probably not spent enough time at this location to undergo sex-change (with spermiogenesis in the gonad) or sterilisation. Similar levels of TBT pollution (high enough to prevent the maintenance of N. lapillus populations) have been reported in Scotland (Harding et al 1997), Ireland (Minchin et al 1997), Spain (Ruiz et al 1998), Norway (Følsvik et al 1999), and Portugal (Barroso & Moreira 2002).…”
Section: Imposex In Nw Brittanymentioning
confidence: 76%
“…However, Fig. 3 indicates that even if there is some input seasonality (probably not widespread because pleasure boating is not popular in the region, see Ruiz et al 1998), it is overcome by the combined use of biomonitors which, by definition, are time-integrators of ambient pollutants. The second obstacle stems from the contrast between the ecology of the mussel (a rocky bottom filter feeder) and the gastropod (a sediment-dwelling detritivore), a disparity that leads to the presumption of different routes of uptake and diverging OT tissue loads.…”
Section: Bioaccumulationmentioning
confidence: 99%
“…There, TBT in Nucella lapillus in 1996 (see Ruiz et al 1998) reached 974 ppb Sn DW, with ΣBTs proportions at 54% (TBT), 36% (DBT) and 10% (MBT). In the present work, mussels (the favourite prey of N. lapillus) at Site 11 show the same decreasing order for ΣBTs proportions, absolute N. lapillus values in summer 1996 doubling those for mussels in autumn 2000 .…”
Section: Bioaccumulationmentioning
confidence: 99%